Analyzing Nike's Concept of Women's Empowerment through Instagram Captions: A Critical Discourse Analysis - Nursagi, Anisa Rizky Nola; Budiwati, Tri Rina; Saad, Nor Azyyati Md (Universitas Ahmad Dahlan, 2023)
Nike, a well-known sports brand, actively uses social media platforms to promote its brand and advocate for social movements, such as women's empowerment. The study aims to use Critical Discourse Analysis (CDA) to analyze Nike's Instagram captions that were posted in 2019 as a way of revealing the essential concept through language and the social practice level. This study uses qualitative research design and critical discourse analysis to analyze Nike's concept towards women in their Instagram captions. The researchers collected data using non-participative observation and purposive sampling techniques and analyzed the data using the referential identity and competence-in-dividing techniques. This study found that it had standard features like vocabulary, grammatical structure, and various textual features. Nike also used discourse practice by employing female athlete representatives to construct the concept of women empowerment in the caption. Furthermore, the language in the caption implied feminist ideology that helped instill the concept of women's empowerment by showing progressivity in the sports industry. The study analyzed Nike's Instagram captions and concluded that the company uses various textual features, including quotations from female athletes, to construct the concept of women's empowerment. Nike's use of persuasive language and representation of feminism ideology supports this concept. This research can have implications for media studies and critical discourse analysis in helping students decode semantic and syntactic choices in media texts.